Multi-media antibiotics, intracellular and extracellular antibiotic resistance genes in marine protected areas of the South China Sea: Spatiotemporal distribution and multi-factor drivers of dissemination - Chengcheng Bu; Limin Ma; Yu Hua; Shaopeng Xu; Yutong Zhang; Huadong Yi; Yuchen Han; Haoyu Zeng; Yongzhi Wang; Xiaoying Xu; Qihui Zhao; Ruolan Jia; et al. (Marine Pollution Bulletin, 2026)

HOPO-functionalized MXene self-supporting membrane for highly efficient and selective uranium extraction from radioactive wastewater - Jiaxin Li; Yinlu Dong; Yu Wang; Xiangcao Chang; Jicui Wen; Yuhang Zhang; Wenhua Zhu; Lichan Xiao; Ruohan Guo; Chaoran Li; Zhiyun Meng; Ruolan Gu; et al. (Chemical Engineering Journal, 2026)

Multi-media distribution, source apportionment, and risk assessment of legacy and current-use organophosphorus pesticides in typical agricultural watersheds of China - Chengcheng Bu; Limin Ma; Weiwei Zhang; Yu Hua; Haoyu Zeng; Yuchen Han; Ruolan Jia; Qihui Zhao; Qi Wang; Yuefei Ruan; Chong Chen (Water Research, 2026)

Occurrence and differential spatiotemporal distribution of pesticides in a plateau lake basin with intensive vegetable cultivation: A case study in Qilu Lake Basin - Qihui Zhao; Limin Ma; Chengcheng Bu; Yu Hua; Ruolan Jia; Chong Chen (Environmental Research, 2026)

Comprehensive single-cell profiling uncovers TsMHC-II expression predicting response to neoadjuvant immunotherapy in gastric cancer - Zhiyuan Xu; Zhichun Tang; Simeng Hu; Litao Yang; Jingli Xu; Pengfei Yu; Yian Du; Yanqiang Zhang; Jiahui Chen; Xiaoxiao Wu; Siwei Pan; ShengJie Zhang; et al. (Science Bulletin, 2026)

Mechanistic differences in ce-MoS2 catalytic activation of peroxides: Pathway divergence and reactive species roles - Shuyun Tai; Lei Sun; Yuxin Wang; Ruolan Huang; Yang Yang; Yu Chen; Hong Chang (Journal of Hazardous Materials, 2025)

Antibiotics, antibiotic resistance genes, and environmental drivers: Assessment of resistance pollution along the Yangtze River Basin - Chengcheng Bu; Chong Chen; Weiwei Zhang; Ru Zhang; Jinpeng Yu; Yu Hua; Haoyu Zeng; Yuchen Han; Ruolan Jia; Qihui Zhao; Yuefei Ruan; Limin Ma (Environmental Pollution, 2025)

Atmospheric and room-temperature plasma mutagenesis enhances the tolerance of Arthrospira platensis to photoinhibition and high-CO2 levels - Ruolan Yuan; Chunli Yu; Rui Xu; Jin Liu; Lina Zhou; Shengxi Shao; Jun Qian; Jingjing Li; Peilun Xu; Wenguang Zhou (Chemical Engineering Journal, 2025)

Hierarchical sulfur vacancy engineering via lattice strain for commercial-grade photocatalytic H2O2 generation in Sm3+-doped ZnIn2S4 - Ruolan Zhao; Chen Chen; Yachao Xu; Yue Qu; Peng Yu; Ying Wang (Chemical Engineering Journal, 2025)

Tidal channel morphology controls on water exchange and sedimentation Patterns: Implications for sustainable reclamation design in semi-enclosed lagoons - Ruolan Yu; Chen Zhang; Zixuan Zhu; Yinzhu Liu (Marine Environmental Research, 2025)

Occurrence and ecological risks of pharmaceuticals along the Yangtze River Basin of China: Insights from target analysis and suspect screening strategy - Chong Chen; Chengcheng Bu; Qi Wang; Yutong Zhang; Shaopeng Xu; Yu Hua; Ruolan Jia; Huiju Lin; Xiaolei Wang; Zhiwei Gan; Xiong Xiong; Limin Ma; et al. (Journal of Hazardous Materials, 2025)

Spatial distribution, phase partitioning, and ecological risk assessment of typical pesticides in Yangtze River Basin - Chengcheng Bu; Chong Chen; Xitong Fu; Weiwei Zhang; Ru Zhang; Yu Hua; Ruolan Jia; Yuefei Ruan; Kenneth Mei Yee Leung; Limin Ma (Journal of Hazardous Materials, 2025)

Optimization of sludge retention time for rapid start-up and stable operation of high-rate partial nitritation in a continuous flow reactor treating municipal wastewater - Ruolan Wen; Min Ye; Yanxu Liu; Chihao Lin; Yu-You Li; Jianyong Liu (Journal of Environmental Management, 2025)

The effect of probiotics supplementation on cancer-treatment complications: a critical umbrella review of interventional meta-analyses - Zhao Yang; Shijie Zhang; Lu Ying; Wenjing Zhang; Xiaoyang Chen; Youfeng Liang; Ruolan Chen; Keying Yao; Chunhui Li; Changyuan Yu; Parmida Jamilian; Meysam Zarezadeh; et al. (Critical Reviews in Food Science and Nutrition, 2025)

Examination of green roofs' cooling effects in a big city based on multi-source remote sensing data: An example from central Xi’an, China - Xiya Yan; Jianhong Liu; Wei Zhang; Ziqi Wang; Ruolan Jia; Lei Wang; Nan Liu; Yu Zhu (Sustainable Cities and Society, 2025)

A chemically enhanced primary treatment and anammox-based process for sustainable municipal wastewater treatment: The advantage and application prospects - Ruolan Wen; Jiayuan Deng; Huan Yang; Yu-You Li; Hui Cheng; Jianyong Liu (Journal of Environmental Management, 2025)

Edge-Based Dynamic Spatiotemporal Data Fusion on Smart Buoys for Intelligent Surveillance of Inland Waterways - Ruolan Zhang; Chenhui Zhao; Yu Liang; Jingfeng Hu; Mingyang Pan (Journal of Marine Science and Engineering, 2025)
Increasing vessel traffic in narrow, winding inland waterways has heightened the risk of accidents, driving the need for improved surveillance and management. This study addresses the challenge of real-time processing and synchronization of voluminous video and AIS data for effective waterway management. We developed a surveillance method utilizing smart buoys equipped with sensors and edge computing devices, enabling dynamic spatiotemporal data fusion. The integration of AIS data with advanced computer vision techniques for target detection allows for real-time traffic analysis and provides detailed navigational dynamics of vessels. The method employs an enhanced Long Short-Term Memory network for precise trajectory prediction of AIS data and a single-stage target detection model for video data analysis. Experimental results demonstrate significant improvements in ship detection accuracy and tracking precision, with an average position prediction error of approximately 1.5 m, which outperforms existing methods. Additionally, a novel regional division and a Kalman filter-based method for AIS and video data fusion were proposed, effectively resolving the issues of data sparsity and coordinate transformation robustness under complex waterway conditions. This approach substantially advances the precision and efficiency of waterway monitoring systems, providing a robust theoretical and practical framework for the intelligent supervision of inland waterways.

The effect of green coffee extract supplementation on obesity indices: critical umbrella review of interventional meta-analyses - Zhao Yang; Zhuo Shao; Weiyi Ouyang; Lu Ying; Rui Guo; Mingxuan Hao; Youfeng Liang; Wenjing Zhang; Xiaoyang Chen; Ruolan Chen; Changyuan Yu; Kousalya Prabahar; et al. (Critical Reviews in Food Science and Nutrition, 2024)

Dicyandiamide addition delay nitrous oxide emission and shift its production pathway from denitrification to incomplete nitrification in maturation phase of composting - Yan Liu; Ruolan Tang; Guoliang Liu; Guoxue Li; Jiani Wang; Yu Cai; Yilin Kong; Jing Yuan (Chemical Engineering Journal, 2024)

Rapid Joule heating-induced welding of silicon and graphene for enhanced lithium-ion battery anodes - Fan Yang; Pengcheng Deng; Hang He; Ruolan Hong; Kun Xiang; Yuan Cao; Beibei Yu; Zeman Xie; Jiming Lu; Zikang Liu; Danish Khan; David Harbottle; et al. (Chemical Engineering Journal, 2024)

Ferroptosis is involved in trophoblast cells cytotoxicity induced by black phosphorus nanoparticles - Ruolan You; Yaming Mu; Jiaqi Zhou; Chunying Wang; Zhenya Fang; Yu Liu; Shiyu Liu; Qingfeng Zhai; Changqing Zhang (Toxicology, 2024)

Plasma-Free Blood as a Potential Alternative to Whole Blood for Transcriptomic Analysis - Qingwang Chen; Xiaorou Guo; Haiyan Wang; Shanyue Sun; He Jiang; Peipei Zhang; Erfei Shang; Ruolan Zhang; Zehui Cao; Quanne Niu; Chao Zhang; Yaqing Liu; et al. (Phenomics, 2024)
RNA sequencing (RNAseq) technology has become increasingly important in precision medicine and clinical diagnostics, and emerged as a powerful tool for identifying protein-coding genes, performing differential gene analysis, and inferring immune cell composition. Human peripheral blood samples are widely used for RNAseq, providing valuable insights into individual biomolecular information. Blood samples can be classified as whole blood (WB), plasma, serum, and remaining sediment samples, including plasma-free blood (PFB) and serum-free blood (SFB) samples that are generally considered less useful byproducts during the processes of plasma and serum separation, respectively. However, the feasibility of using PFB and SFB samples for transcriptome analysis remains unclear. In this study, we aimed to assess the suitability of employing PFB or SFB samples as an alternative RNA source in transcriptomic analysis. We performed a comparative analysis of WB, PFB, and SFB samples for different applications. Our results revealed that PFB samples exhibit greater similarity to WB samples than SFB samples in terms of protein-coding gene expression patterns, detection of differentially expressed genes, and immunological characterizations, suggesting that PFB can serve as a viable alternative to WB for transcriptomic analysis. Our study contributes to the optimization of blood sample utilization and the advancement of precision medicine research.

Chemometrics-based investigation of non-volatiles/volatiles flavor of tencha (Camellia sinensis cv. Yabukita, Longjing 43 and Baiye 1) - Qiuwen Yu; Chuangsheng Huang; Ruolan Zhu; Debiao Lu; Liping Liu; Jianhong Lai; Xinyao Zhong; Jueshan Guan; Senjie Zhou; Yilin Tong; Zipei Wang; Ping Chen; et al. (Food Research International, 2023)

Induction of Anxiety-Like Phenotypes by Knockdown of Cannabinoid Type-1 Receptors in the Amygdala of Marmosets - Lin Zhu; Di Zheng; Rui Li; Chen-Jie Shen; Ruolan Cai; Chenfei Lyu; Binliang Tang; Hao Sun; Xiaohui Wang; Yu Ding; Bin Xu; Guoqiang Jia; et al. (Neuroscience Bulletin, 2023)

Stagnant water environmental management in urban river networks: An integrated risk analysis involving hydraulic potential dissipation - Ruolan Yu; Chen Zhang; Xueping Gao; Kensey Daly (Journal of Hydrology, 2023)

Impact of battery electric vehicles on ventilation design for road tunnels: A review - Xu Wang; Mingnian Wang; Ruolan Jiang; Jiani Xu; Bingtian Li; Xiao Wang; Mingyu Lei; Pengfei Su; Chaopeng Liu; Qianru Yang; Jianle Yu (Tunnelling and Underground Space Technology, 2023)

Enhanced dandelion phytoremediation of Cd-contaminated soil assisted by tea saponin and plant growth-promoting rhizobacteria - Jie Yu; Ruolan Xie; Jiang Yu; Huan He; Siwei Deng; Senxu Ding; Xiaoshuang Sun; Hameed Hllah (Journal of Soils and Sediments, 2023)

The combined effect of titanium dioxide nanoparticles and cypermethrin on male reproductive toxicity in rats - Yuxin Li; Mingqing Zhong; Xianzhi He; Ruoyu Zhang; Yu Fu; Ruolan You; Feiyan Tao; Lei Fang; Yuanyuan Li; Qingfeng Zhai (Environmental Science and Pollution Research, 2022)

Aquaporin 5 is degraded by autophagy in diabetic submandibular gland - Yan Huang; Xijin Shi; Qianying Mao; Yan Zhang; Xin Cong; Xueming Zhang; Zhejing Zhang; Liling Wu; Ruolan Xiang; Guangyan Yu (Science China Life Sciences, 2018)